Past and presentism: the 'precolonial' and the foreshortening of African history - Reid, R (Cambridge University Press, 2011)
This article considers the marginalization of precolonial history from mainstream Africanist scholarship in recent decades, and argues that this can be understood in the context of a scholarly culture that attributes an exaggerated significance to the history of the twentieth century. The article highlights some of the work that continues to be done on Africa's deeper past, with a view to demonstrating the enormous value of such research in elucidating present-day issues. It also argues, however, that work on the modern period is preponderant, and that there is a clear tendency toward historical foreshortening, evidenced in recent scholarship on such topics as conflict and ethnicity.